訪問歯科診療における口内法X線撮影 - 岡野 恒一; 清水 康行; 奥村 信次; 中村 守厚; 有地 榮一郎 (Shika Hoshasen, 2006)
The demand for visiting dental care has been increasing in Japan. However, intra-oral radiographs are not frequently obtained from bedridden patients regardless of whether they are at home or in hospital. In 1998, we started a project to establish a systematic method of dental radiography for bedridden elderly. In the present study, we analyzed 60 bedridden patients receiving dental treatment and examination by intra-oral radiography between 1998 and 2000. Subjects consisted of 32 females and 28 males with an average age of 75.6 years. According to the standard for assessment of independence in daily life, 2 patients were classified in Rank J (independent in daily life activities), 3 in Rank A (house-bound : needing partial assistance only in outdoor activities), 26 in Rank B (chair-bound : needing partial assistance only in indoor activities) and 29 in Rank C (bed-bound : dependent for most daily activities). Most patients were the so-called “bedridden elderly” classified in Rank B or C. In the majority of patients (56%), the cause of becoming bedridden was cerebrovascular disease. The dental diseases were caries, periodontitis, alveolar abscess and so on. All intra-oral radiographs were taken with a portable X-ray unit and an indicators which enabled the operator to fold film and set an adequate beam projection. A total of 291 radiographs were obtained. These radiographs were retrospectively evaluated by two observers and were classified as good or poor quality. Good quality was defined as an image showing sufficient quality for clinical use. When the judgment differed between the two observers, a consensus was reached after discussion. There were no differences in the number of images obtained among Ranks for independence in daily life. The radiographs obtained in Rank C patients or in those who could not communicate with treatment staff showed poor quality. As the major cause of poor quality was failure in the holding film, improvement of the indicator was considered necessary.